2017
DOI: 10.4236/jbbs.2017.710034
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dimethoate Exposure on Locomotor Activity and Anxiety-Like Behavior in Female Wistar Rat

Abstract: Developmental exposure to organophosphate insecticide is well known to induce neurobehavioral impairments, at late period. The present study aims to investigate the effects of subchronic exposure to Dimethoate, on locomotors skills and anxiety like behavior among wistar rat. Two groups of female's rats are used. The intoxicated group receives daily, during five weeks, by intragastric gavage, a dose of Dimethoate dissolved in corn oil (100 mg/kg body weight). The control group receives only the corn oil. Sponta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…Thus, human exposure to it can result from environmental, occupational, or accidental exposure [9]. Similarly to Cd, various studies have suggested that exposure to organophosphate insecticides, including DM, are associated with increased anxiety [10] and damage of motor activity and performance [11]. Interestingly, these effects are associated with inhibition of the AChE enzyme since organophosphate insecticides are classic inhibitors of this enzyme [12] although other environmental agents, such as Cd for example, also inhibit their activity [13].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, human exposure to it can result from environmental, occupational, or accidental exposure [9]. Similarly to Cd, various studies have suggested that exposure to organophosphate insecticides, including DM, are associated with increased anxiety [10] and damage of motor activity and performance [11]. Interestingly, these effects are associated with inhibition of the AChE enzyme since organophosphate insecticides are classic inhibitors of this enzyme [12] although other environmental agents, such as Cd for example, also inhibit their activity [13].…”
Section: Introductionmentioning
confidence: 99%